Community Economic Recovery Strategy During The Covid-19 Pandemic Through Optimalization of Rural Economic Potential in Licin District, Banyuwangi Regency - Kanthi Pangestuning Prapti (UPT Penerbitan Universitas Jember, 2021)
The current covid-19 pandemic has an impact on various sectors of the economy. Licin subdistrict is one of the subdistricts in Banyuwangi regency that has considerable potential in the agricultural sector, small and medium micro enterprises (SMEs), and tourism. This potential can be used as an economic booster for the main community in Licin District in the current covid pandemic. This study aims, among others, a) to know the economic potential of the village in Licin District; b) identify the impact of covid-19 on the community economy in Licin District, and c) formulate a strategy for economic recovery during the pandemic based on the economic potential of the village in Licin District. The research uses the SWOT method to identify internal and external factors of economic potential, as well as the AHP method to determine the necessary strategy alternatives. Based on the results of the study, it can be seen that the impact on the agricultural sector, among others: almost no effect on demand, rising production costs, increased shipping costs, and the supply chain process is disrupted due to disrupted logistics distribution. Impacts on the SME sector include: weakening of public purchasing power, decreased turnover, increased shipping costs, rising prices of some business raw materials, reduced production of goods, and supply chain process disrupted due to disrupted logistics distribution. While the impact on the tourism sector is a decrease in the number of tourists so which causes businesses that support the tourism sector to be weakened (travel agents, tour guides, restaurants, hotels, homestays). The priorities of the proposed strategy from the most important to the lowest level of interest are to build cooperation with stakeholders, integrated agricultural management with sustainable technology, strengthening the institutions of BUMDES by optimizing the participation rate of productive age, Adaptation, and innovation of SMEs with the use of digital technology. Keywords: Village potential, Covid-19 impact, Strategy, Economic recovery.